Intermittent preventive treatment in pregnant women is associated with increased risk of severe malaria in their offspring. - Whitney E Harrington (PLoS ONE, 2013)
BACKGROUND:In areas of widespread sulfadoxine-pyrimethamine resistance, intermittent treatment in pregnancy (IPTp) fails to prevent placental malaria (PM) and may exacerbate drug resistant infections. Because PM predicts increased susceptibility to parasitemia during infancy, we hypothesized that IPTp would also increase susceptibility to malaria infection and disease in the offspring. METHODS:In a birth cohort from NE Tanzania, we evaluated the association between maternal IPTp use and risk of parasitemia and severe malaria in the offspring. Using Cox Proportional Hazards Models as well as Generalized Estimating Equations, we evaluated the effects of IPTp on the entire cohort and on subgroups stratified by PM status at delivery. RESULTS AND CONCLUSIONS:Offspring of PM+ women who received IPTp had a dose-dependent decrease in time to first parasitemia (AHR = 2.13, p = 0.04 [95%CI: 1.04, 4.38]). Among all offspring, IPTp was associated with earlier first severe malaria episode (AHR = 2.32, p = 0.02 [95%CI: 1.12, 4.78]) as well as increased overall odds of severe malaria (AOR = 2.31, p = 0.03 [95%CI: 1.09, 4.88]). Cost-benefit analyses of IPTp regimens should consider the long term effects on offspring in addition to pregnancy outcomes.